Community empowerment through improvements skills and health promotions on refugees in the Medan district of Selayang - Santi, Devi Nuraini; Lubis, Halinda Sari (Talenta Publisher, 2020)
Empowerment means empowering a person because he is considered to be helpless or very small, so that he can hardly do anything, women refugees need to be empowered by providing skills that produce economic value and filling free time aimed at reducing levels stress on refugees. One that can be used as a skill material is the production which is currently experiencing an increase in patchwork waste. There were 182 refugees in Medan Selayang Subdistrict, and 52 adult women in particular. The principle of service that will be carried out for partners in Kost YPAP refugee camps is to provide health promotion, guidance and skills in processing patchwork into economic value goods, so that refugees have skills that can be applied while in refugee with economic value and can reduce stress on refugees. The Community Service Team conducted socialization on the empowerment of refugee women specifically in producing accessories from varied patchwork and beads as well as health promotion in reducing stress levels due to lack of activity and limited activities on refugees. Furthermore, the Community Service Team conducts training to improve knowledge and skills in order to obtain high sales value in the community and its marketing is assisted by the Social Service and the National Conference in Medan.